Differential involvement of hypothalamic vasopressin neurons in multiple system atrophy - Benarroch, Eduardo E.; Schmeichel, Ann M.; Sandroni, Paola; Low, Phillip A.; Parisi, Joseph E. (Brain (London, England : 1878), 2006)
We sought to determine whether there is differential involvement of different groups of hypothalamic arginine-vasopressin (AVP) synthesizing neurons in multiple system atrophy (MSA). Hypothalamus was obtained from five subjects with clinical diagnosis of MSA confirmed neuropathologically and five age-matched controls. Sections were immunostained for AVP, and cells with visible nuclei were counted in the posterior portion of the paraventricular nucleus (PVNp), supraoptic nucleus (SON), magnocellular PVN and suprachiasmatic nucleus (SCN). Sections of the hypothalamus and medulla were also immunostained for tyrosine hydroxylase (TH). There was a significant loss of AVP neurons in the PVNp in MSA compared with controls (17 ± 3 versus 59 ± 10 cells/section, P < 0.01). There was preservation of AVP- and TH-immunoreactive neurons in the SON and magnocellular PVN in all MSA cases. In contrast, there was marked depletion of TH-immunoreactive fibres innervating these magnocellular AVP neurons, coincident with a loss of neurons in the A1 area (6 ± 1 versus 13 ± 1 cells/section, P < 0.01). There was loss of AVP neurons in the SCN in MSA compared with control cases (14 ± 3 versus 71 ± 16 cells/section, P < 0.02). Our results indicate that, in MSA, loss of AVP neurons in the PVNp may contribute to sympathetic failure, whereas loss of catecholaminergic input from the brainstem to the magnocellular AVP neurons may contribute to impaired AVP secretion in response to orthostatic stress. Loss of AVP neurons in the SCN may contribute to impaired circadian regulation of endocrine and autonomic functions.